IMPLEMENTASI SOLAR CHARGING STATION DAN DIGITALISASI SISTEM LELANG HASIL PANEN UNTUK MENINGKATKAN JUMLAH PENGUNJUNG DI EMBUNG SENDANGTIRTO - Haeni Budiati; Lukas Agung Heriputranto; Liefson Jacobus (LPPM Universitas Bina Bangsa, 2023)
Sendangtirto Village is located in Kapanewon Berbah, Sleman D.I. Regency. Yogyakarta has an artificial reservoir/lake. The main objective of building a reservoir is to provide a conservation area and irrigation of rice fields. The existence of harvest sales activities through an auction system and the construction of joglos and gazebos around the embung, make the Sendangtirto embung worthy of becoming a tourist destination. Currently, the existence of the embung is not yet known to the wider public, besides that the public facilities available are still minimal. The PKM team took the title